1998
DOI: 10.1002/(sici)1096-8628(19981204)80:4<356::aid-ajmg10>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Absence of correlation between skewed X inactivation in blood and serum creatine‐kinase levels in Duchenne/Becker female carriers

Abstract: The pattern of X inactivation in lymphocyte DNA was investigated in 107 Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) carriers (102 asymptomatic and 5 manifesting carriers) and 117 normal female controls of different ages, with the aim: a) to analyze the pattern of X inactivation in blood DNA of a large number of DMD/BMD carriers as compared to normal female controls; b) to determine if there is a decrease in serum creatine kinase (CK) levels with age in obligate DMD/BMD carriers; c) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 0 publications
1
23
0
1
Order By: Relevance
“…In the two largest reported series of DMD carriers, the proportion of manifesting carriers varied from 5 to 22% and the pediatric cases remained rare. 4,20 In our patients, like in the other pediatric series, hyperCKemia was constant. [27][28][29][30] Muscle weakness was also prevalent and found in 88% of cases.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the two largest reported series of DMD carriers, the proportion of manifesting carriers varied from 5 to 22% and the pediatric cases remained rare. 4,20 In our patients, like in the other pediatric series, hyperCKemia was constant. [27][28][29][30] Muscle weakness was also prevalent and found in 88% of cases.…”
Section: Discussionsupporting
confidence: 79%
“…18 However, whereas it is widely accepted that X-chromosome inactivation (XCI) has a role in the clinical variability in DMD carriers, XCI seems to be insufficient to predict the phenotypic status and degree of muscle weakness in young DMD carriers. 19,20 To better understand the mechanisms of this variability, we reviewed clinical, histological and genetic parameters including XCI pattern of 26 early pediatric symptomatic DMD carriers.…”
Section: Introductionmentioning
confidence: 99%
“…In other Xlinked recessive disorders, differences between clinical phenotypes of female carriers and the X-inactivation ratios in peripheral blood were found. Sumita et al [20] reported that no significant correlation was found between the X-inactivation ratio in blood and serum CK activity in Duchenne/Becker muscular dystrophy carriers. Orstavik et al [21] reported that the wide range in plasma concentration of factor VIII and IX in haemophilia A and B carriers could not be explained by the X chromosome inactivation patterns in peripheral blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, another study comprising 107 MD carriers clearly suggested that a highly skewed X-chromosome pattern in blood is not enough to predict the phenotypic development of muscular weakness in MD carriers. 4 Hence, we think that not performing this analysis in the reported patients was justified.…”
mentioning
confidence: 98%
“…In contrast, another study comprising 107 MD carriers clearly suggested that a highly skewed X-chromosome pattern in blood is not enough to predict the phenotypic development of muscular weakness in MD carriers. 4 Hence, we think that not performing this analysis in the reported patients was justified.Classifying cardiomyopathy on the basis of ejection fraction may only underestimate the extent of disease that is most evident in patients with hypertrophic cardiomyopathy. In our opinion, both mother and child have advanced cardiomyopathy because late gadolinium enhancement (LGE) cardiovascular MRI already revealed significant myocardial tissue damage (LGE in the child, 12.0%; in the mother, 17.6% of left ventricular mass).…”
mentioning
confidence: 99%